Welding Quality Control Using Statistical Quality Control (SQC) Methods and Failure Mode Effect Analysis (FMEA) at PT. XYZ - Rr. Rochmoeljati; Isna Nugraha; Nafa Artha Cahaya Mulia (Nusantara Science and Technology Proceedings, 2022)
PT XYZ is the largest shipbuilding company in Indonesia. The company's products are shipbuilding and ship design based on consumer demand. In the production process of the BRS W-303 ship, defects were still found during welding, such as incomplete penetration and slag inclusion. The purpose of this study was to determine the percentage of the most dominant defects and the factors causing defects and to provide suggestions for improving the quality of welding. The methods used are Statistical Quality Control (SQC) and Failure Mode Effect Analysis (FMEA). SQC tools are check sheets, stratification, scatter diagrams, attribute control charts, and cause and effect diagrams. Then continue the FMEA analysis based on the cause-and-effect diagram for proposed improvements. Based on the results of Statistical Quality Control (SQC) research, it is known that the most dominant ship welding defects are incomplete penetration (32.81%) and slag inclusion (23.26%). Based on the results of research on Failure Mode Effect Analysis (FMEA) it is known that the root cause of the highest problem with RPN 288 is the determination of the root gap is too small or narrow. Recommendations for improvement that can be proposed are to ensure that the welder must read and understand the WPS used to weld correctly.